A novel and effective method to fabricate flame retardant and smoke suppressed flexible polyurethane foam1. Issue 83 (9th September 2015) - Pan, Ying; Zhan, Jing; Pan, Haifeng; Wang, Wei; Ge, Hua; Song, Lei; Hu, Yuan
<x xml:space="preserve">Abstract</x> In the present work, magnesium hydroxide were successfully deposited on the surface of flexible polyurethane foam to suppress its flammability and smoke production.